If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7 = -36 Reorder the terms: 7 + 3x = -36 Solving 7 + 3x = -36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3x = -36 + -7 Combine like terms: 7 + -7 = 0 0 + 3x = -36 + -7 3x = -36 + -7 Combine like terms: -36 + -7 = -43 3x = -43 Divide each side by '3'. x = -14.33333333 Simplifying x = -14.33333333
| 8x-5=7-4x | | x/3-4=7 | | x(3x-y)(4x+5y)= | | -17+11+6=7t | | 2x+8=-48 | | 7xy^4-7xy^2=0 | | 3n^2-3n-36=0 | | 5(5x+3)=3(8x-2+4) | | x(3x-y)(4x+5x)= | | -7+11+6=7t | | 2x+25=-2x-7 | | 6(x-2)=14 | | 3x-39=75 | | 5=7t | | -4x+(-2x+6)=9 | | 13x+23=2x-13 | | -3x-8=x+16 | | -6x+2(x+6)=42 | | k-5k=-40 | | -3x-19=5+x | | -3x-19=5+5 | | 2x-1/4=5 | | x-1+7x+55=2x-1 | | (2x+y)(x^2+3xy-2y^2)= | | -4x+4(-4x-11)=46 | | 0.2x+2.4=1.5+1.2x | | (5x^2+8x)(15x^2-7x-4)=0 | | 2-6(a-7)=-(1+a) | | 3x+10=-5-2x | | x^2+4x-36=0 | | 6n=4(n+5)+2n | | 10[z-(9z+42)+2]=5z+25 |